The Impact of Intermittent Fasting: Enhancing Health and Mitigating Disease Risks - Alicja Grzelak (Journal of Education, Health and Sport)
Introduction: Intermittent fasting (IF) has emerged as a popular dietary intervention for its potential health benefits, including weight management, metabolic improvement, and reduced risk of chronic diseases. The practice alternates periods of eating and fasting, influencing physiological processes and offering an alternative to traditional calorie-restrictive diets.